Bioremediation of petroleum hydrocarbon in Antarctica by microbial species: an overview - Abdul Habib, Nur Muhamad Syahir; Ahmad, Siti Aqlima; Wan Johari, Wan Lutfi; Abd. Shukor, Mohd. Yunus; Yasid, Nur Adeela (Universiti Putra Malaysia Press, 2018)
The increase of anthropogenic activities and growth of technology in Antarctica is fuelled by the high demand for petroleum hydrocarbons needed for daily activities. Oil and fuel spills that occur during explorations have caused hydrocarbon pollution in this region, prompting concern for the environment by polar communities and the larger world community. Crude oil and petroleum hydrocarbon products contain a wide variety of lethal components with high toxicity and low biodegradability. Hydrocarbon persistence in the Antarctic environment only worsens the issues stemming from environmental pollution as they can be long-term. Numerous efforts to lower the contamination level caused by these pollutants have been conducted mainly in bioremediation, an economical and degrading-wise method. Bioremediation mainly functions on conversion of complex toxic compounds to simpler organic compounds due to the consumption of hydrocarbons by microorganisms as their energy source. This review presents a summary of the collective understanding on bioremediation of petroleum hydrocarbons by microorganisms indigenous to the Antarctic region from past decades to current knowledge.